Β-Sheet Augmentation Is a Conserved Mechanism of Priming HECT E3 Ligases for Ubiquitin Ligation. Issue 18 (14th September 2018) - Jäckl, Magnus; Stollmaier, Carsten; Strohäker, Timo; Hyz, Karolina; Maspero, Elena; Polo, Simona; Wiesner, Silke
Abstract: Ubiquitin (Ub) ligases (E3s) catalyze the attachment of Ub chains to target proteins and thereby regulate a wide array of signal transduction pathways in eukaryotes. In HECT-type E3s, Ub first forms a thioester intermediate with a strictly conserved Cys in the C-lobe of the HECT domain and is then ligated via an isopeptide bond to a Lys residue in the substrate or a preceding Ub in a poly-Ub chain. To date, many key aspects of HECT-mediated Ub transfer have remained elusive. Here, we provide structural and functional insights into the catalytic mechanism of the HECT-type ligase Huwe1 and compare it to the unrelated, K63-specific Smurf2 E3, a member of the Nedd4 family. We found that the Huwe1 HECT domain, in contrast to Nedd4-family E3s, prioritizes K6- and K48-poly-Ub chains and does not interact with Ub in a non-covalent manner. Despite these mechanistic differences, we demonstrate that the architecture of the C-lobe Ub intermediate is conserved between Huwe1 and Smurf2 and involves a reorientation of the very C-terminal residues. Moreover, in Nedd4 E3s and Huwe1, the individual sequence composition of the Huwe1 C-terminal tail modulates ubiquitination activity, without affecting thioester formation. In sum, our data suggest that catalysis of HECT ligases hold common features, such as the β-sheet augmentation that primes the enzymes for ligation, and variable elements, such as the sequence of the HECT C-terminal tail, that fine-tune ubiquitination activity and may aid in determining Ub chain specificity by positioning the substrate or acceptor Ub. Graphical Abstract: Unlabelled Image Highlights: The Huwe1 ligase synthesizes K6- and K48-linked ubiquitin chains. The structural features of thioester intermediates are conserved between K63-specific Nedd4 family ligases and Huwe1. NMR data provide evidence for conformational changes of the C-terminal residues upon transthiolation. The catalytic mechanisms of HECT domains seem to diverge after thioester formation.